Large Cryptococcus neoformans isolated from brain abscess. - Love, G L (1985)
Cryptococcus neoformans yeast cells 40 to 60 micron in diameter were seen in an India ink preparation made from a human brain abscess specimen. In culture at 25 degrees C, uniform 5-micron-diameter yeast cells were produced. Inoculation into mice produced yeast cells up to 40 micron in diameter, and brain heart infusion broth culture at 35 degrees C produced yeast cells about 25 micron in diameter. A relationship of yeast cell diameter to incubation temperature is suggested.